Identification of dendrobium Natural Orchids in Liwa Botanical Garden based on leaf morphological characters - Mahfut Mahfut; Tundjung Tripeni Handayani; Sri Wahyuningsih; Sukimin Sukimin (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Lampung Indonesia is one of the provinces on the island of Sumatra, which has a flora conservation area located in Liwa Botanical Garden, West Lampung Regency. One of the flora species in the area with a high level of diversity is the orchid plant. The Dendrobium is the largest orchid species, where the public widely hunts this orchid for an economic reason due to the beauty of its various flower shapes and colors. Given the high level of human encroachment, this can threaten the existence of natural orchid plants, causing loss of their original habitat and causing the extinction of orchid species. Based on data in Liwa Botanical Garden, there has been no further identification of natural orchids as a plant conservation effort. To protect and immediately save these natural orchids, it is necessary to identify the Dendrobium orchid species based on the leaf morphological approach. This research will be conducted in April-September 2020. Observations of leaf morphology include leaf shape, leaf tip shape, leaf base shape, leaf edge, leaf reinforcement, leaf arrangement, leaf surface texture, leaf symmetry, and leaf sitting based on guidelines for ornamental plant characterization books. Observations as secondary data were added to the character of the pseudobulb shape and orchid habitat. Observations as secondary data were added on the habitat character of pseudobulbs and orchids. The implementation of this activity is still in the period of the Covid-19 pandemic, so most of the activities are carried out online. The coaching and training phase was conducted through internal virtual discussions on Tuesday, July 7, 2020, while the coaching phase was conducted through meetings or verbal communication via telephone groups and WhatsApp. Based on the evaluation data, it is known that there is an increase in knowledge and understanding of training participants by 21.64 points. The percentage increase in value before and after training is 34.72%. Orchid-related activities at Liwa Botanical Garden were never carried out, thus imparting knowledge to Liwa Botanical Garden technicians and workers on the development of natural orchid identification methods based on the morphological character in local natural resource conservation in the 4.0 industrial revolution era.